Case Report: A Novel Splice-Site Mutation in DNAJB6 Associated With Juvenile-Onset Proximal–Distal Myopathy in a Chinese Patient - Ji, Guang; Wang, Ning; Han, Xu; Wang, Yaye; Zhang, Jinru; Wu, Yue; Wu, Hongran; Ma, Shaojuan; Song, Xueqin (Frontiers in Genetics, 2022)
DNAJB6 was identified as the causative gene of limb-girdle muscular dystrophy type 1D. In recent years, the phenotypic and molecular spectrum of DNAJB6-myopathy has been expanded and several mutations of DNAJB6 have been identified in Europe, North America, and Asia. Interestingly, almost all identified mutations were point mutations in previous reports and most were clustered in exon 5 which encodes the G/F domain of DNAJB6. The so-far unique splice site mutation eliminating the entire G/F domain was reported to cause a severe, early-onset phenotype. Here we report a juvenile-onset Chinese patient who presented with proximal-distal myopathy as well as esotropia and facial weakness. Muscle pathology showed rimmed vacuolation and myofibrillar disarrangement. A novel splice-site mutation NM_058246:c.236-1_240delGGTGGA of the DNAJB6 gene was identified by targeted exome sequencing which result in a severe defect of the G/F domain. This rare mutation type expands the molecular spectrum of DNAJB6-myopathy and further underlines the importance of the G/F region.